2016
DOI: 10.1016/j.ajpath.2016.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Ornithine Decarboxylase Is Sufficient for Prostate Tumorigenesis via Androgen Receptor Signaling

Abstract: Increased polyamine synthesis is known to play an important role in prostate cancer. We aimed to explore its functional significance in prostate tumor initiation and its link to androgen receptor (AR) signaling. For this purpose, we generated a new cell line derived from normal epithelial prostate cells (RWPE-1) with overexpression of ornithine decarboxylase (ODC) and used it for in vitro and in vivo experiments. We then comprehensively analyzed the expression of the main metabolic enzymes of the polyamine pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 57 publications
2
24
0
Order By: Relevance
“…We also observed decreased levels of myoinositol, inosine, adenosine, asparagine, aspartate, and guanosine, which have been previously reported as being depleted in metastatic PC tissue 49 , indicating that activation of OR51E2 by agonists in LNCaP cells produces metabolic signatures similar to those observed in human metastatic tissues. Agonist treatment also reduced levels of intracellular urea and spermine/spermidine, in accordance with recently reported data showing reduced spermine during malignant transformation 63 . Accordingly, we also detected decreased intracellular levels of ornithine, a precursor of polyamines.…”
Section: Metabolomic Signatures Of Lncap Cells Treated With Selected supporting
confidence: 92%
“…We also observed decreased levels of myoinositol, inosine, adenosine, asparagine, aspartate, and guanosine, which have been previously reported as being depleted in metastatic PC tissue 49 , indicating that activation of OR51E2 by agonists in LNCaP cells produces metabolic signatures similar to those observed in human metastatic tissues. Agonist treatment also reduced levels of intracellular urea and spermine/spermidine, in accordance with recently reported data showing reduced spermine during malignant transformation 63 . Accordingly, we also detected decreased intracellular levels of ornithine, a precursor of polyamines.…”
Section: Metabolomic Signatures Of Lncap Cells Treated With Selected supporting
confidence: 92%
“…ODC is a focus of therapies that aim to prevent carcinogenesis because it is a transcriptional target of a proto-oncogene [ 344 , 345 , 346 ], and many studies have shown that transfection of the ODC gene results in increased intracellular polyamine levels and malignant transformation [ 347 , 348 , 349 , 350 , 351 , 352 , 353 ]. Most reports on the roles of ODC in malignant transformation have examined cells that were already at risk of tumorigenesis.…”
Section: Possible Role Of Polyamines In Inhibiting Tumorigenesismentioning
confidence: 99%
“…In combination with other pro-cancerous events such as expression of a mutated Ras oncogene ODC promotes invasiveness of skin cancer cells [ 122 ]. Overexpression of this enzyme in normal prostate cells is sufficient for their malignant transformation [ 123 ]. In this study, a strong up-regulation of the main polyamine enzymes (ODC, spermine oxidase, spermine synthase) and a concomitant reduction of spermine was observed in high-grade prostate intraepithelial neoplasia (HGPIN) tissues as compared to normal prostate glands with the expression levels for SMOX expression being the highest.…”
Section: Biogenic Polyamines At the Crossroads Of Redox Statusmentioning
confidence: 99%